FLEXIBILITY AND TENDON: A BRIEF REVIEW - Cini, Anelize (2022)
Performing flexibility training in an exercise program is important to improve range of motion (ROM). However, most of the evaluation of flexibility is restricted to joint movement, which does not allow the identification of the mechanisms that cause the increase of ROM. It is known that, when passive movement occurs in a joint, the tendon is responsible for part of the deformation observed in the muscle complex that is the antagonist of the evaluated movement. Therefore, understanding the best prescription and frequency of flexibility exercise leads to changes in tendon properties is essential for an appropriate and effective exercise routine. Thus, the aim of this review was to organize and discuss publications about the implications of triceps surae stretching in ROM, as well as its influence on tendon properties. Acute studies show that continuous stretching times between five and 10 minutes cause decreased tendon stiffness, which is not seen in fractionated stretching times less than five minutes. Chronic studies, in turn, also don’t present significant results in stiffness with fractionated times and studies with continuous times were not found. Thus, it is not possible to know if a continuous stretching time (longer than one minute) or a total time longer than five minutes but fractionated, can influence the tendon stiffness.